Uncovering the Drivers of Utility Performance : Lessons from Latin America and the Caribbean on the Role of the Private Sector, Regulation, and Governance in the Power, Water, and Telecommunication Sectors - Andrés, Luis A. (Washington, DC: World Bank, 2013)
This book conducts a micro-level analysis of various determinants of infrastructure sector performance that affect development. This book focuses on the distribution segment of three basic infrastructure services: electricity, water and sanitation, and fixed telecommunications. This books aims to answer four main sets of questions: what are the main performance trends in the region, and how heterogeneous are they?; how does the performance of state-owned and private utilities differ?; how does the institutional design of regulatory agencies affect sector performance?; and what management mechanisms create incentives for improved performance?. This book begins by describing the main elements that characterize sector performance, defined as the delivery of reliable, affordable service that complies with certain quality standards. It focuses on the relationship between sector performance and the following determinants: private sector participation, regulatory agencies, and corporate governance. It also examines related aspects, such as contract design, market structure, and, for telecommunications, market competition. This book first explains the dynamics of utility performance and the interactions between key internal variables and utility performance in each sector. The book is organized as follows: chapter one is introduction. Chapter two outlines changes in the electricity distribution, water and sanitation, and fixed telecommunications sectors in the Latin America and the Caribbean (LAC) region over the past 15 years. This chapter tells multiple stories of the substantial improvement in these sectors and fills in knowledge gaps by benchmarking utility performance at the regional, country, and utility levels. Chapter three synthesizes the impact private sector participation has had on electricity distribution, water and sewerage, and fixed-line telecommunications. This chapter also identifies whether private sector participation characteristics such as the sale method; investor nationality; and award criterion affect performance. Chapter four explores the institutional design of regulatory agencies and the link between regulatory governance and sector performance. Chapter five assesses the governance of state-owned enterprises (SOEs) in infrastructure, based on survey results from 45 SOEs in the water and electricity distribution sector of LAC. Chapters six examines other potential determinants for sector performance, including corruption, cost recovery, contract arrangements, and competition. Chapter seven summarizes the book s main results and describes the array of possibilities for moving forward.